Utility and Predictive Value of Human Standard Semen Parameters and Sperm DNA Dispersion for Fertility Potential - Gill, Kamil (Int J Environ Res Public Health, 2019)
Because the assessment of sperm DNA fragmentation (SDF) plays a key role in male fertility, our study was designed to find the relationships between SDF and standard semen parameters. The receiver operating characteristic (ROC) curve showed that 18% SDF is a prognostic parameter for discriminating between men with normal and abnormal standard semen parameters (n = 667). Men with > 18% SDF had significantly lower quality semen, a higher prevalence of abnormal semen characteristics, and a higher odds ratio for abnormal semen parameters compared to men with ≤ 18% SDF. An ROC analysis provided predictive values for age and semen parameters to distinguish between men with SDF > 18% and men with ≤ 18% SDF. SDF was positively correlated with male age and teratozoospermia index but negatively with sperm concentration, total number of spermatozoa, sperm morphology, progressive motility, and vitality. Our study shows that 18% SDF has a predictive value for distinguishing between men with normal and abnormal semen characteristics. Men with >18% SDF have a higher risk for abnormal semen parameters, while age and obtained semen parameters have a predictive value for SDF. There is a relationship between SDF and conventional sperm characteristics, and thus, SDF can be incorporated into male fertility assessment.